A Pilot Study of An Intervention to Increase Family Member Involvement in Nursing Home Care Plan Meetings. (September 2021) - Oliver, Debra Parker; Rolbiecki, Abigail J.; Washington, Karla; Kruse, Robin L.; Popejoy, Lori; Smith, Jamie B.; Demiris, George
Background and Objectives: Many family members struggle to negotiate their aging relative's care with nursing home staff, potentially leading to depression and other negative outcomes for residents' families. This pilot study tested an intervention designed to empower residents' family members to attend and participate in nursing home care plan meetings. Research Design and Methods: We conducted a small, randomized, controlled trial of the Families Involved in Nursing home Decision-making (FIND) intervention, which used web conferencing to facilitate family participation in care plan meetings. Results: Overall, FIND was feasible and acceptable. Family members who received the FIND intervention were more likely to experience decreased depressive symptoms than those who did not. Discussion and Implications: FIND is a promising approach to reduce depression among family members of nursing home residents. Findings support the need for a follow-up clinical trial.